Exploring the Spatial Patterns of Accessibility to Metro Services Considering the Locations of Station Entrances/Exits - Congxiao Yan; Yueer Gao; Yifu Yang (Buildings)
Accessibility to metro services is often evaluated based on the locations of stations. However, compared to the location of station itself, focusing on its entrances/exits offers a more accurate approach to assessing station supply and demand levels. Despite this, research focusing on the supply of and demand for metro services concerning metro entrances and exits remains limited. This study employed multi-source geospatial data from Xiamen, China, to examine the supply and demand dynamics of metro stations with a particular emphasis on entrances/exits. In the first phase, we treated entrances/exits as supply facilities and used land plot boundaries as the fundamental spatial units for accessibility calculations. Taking into account the layout characteristics of entrances/exits, along with the traffic generation of various land-use types, we employed the Gaussian two-step floating catchment area (G2SFCA) method to gauge the supply and demand levels of plots. Subsequently, we computed the spatial supply-and-demand relationships of station entrances/exits for both station-level and shared usage level of entrances/exits. We found that the accessibility from plots to entrances/exits diverged from previously observed spatial distribution trends, being higher in city centers, regional boundaries, and terminal stations and lower in transitional areas. Moreover, “metro accessibility” and the “imbalance index of entrances/exits” are associated with the primary functions of stations and the surrounding urban development; yet they exhibit spatial heterogeneity. The stations with a high value for “imbalanced index of entrances/exits” were always near some business parks, and “metro accessibility” seemed to be more easily affected by location factors. Based on two metrics, stations were categorized into four types, each displaying unique characteristics regarding location distributions, entrance/exit configurations, and commuting passenger sources. This research aims to identify the phenomenon of unfair transport in metro service from the perspective of their entrances, inform the optimization of metro station designs, and tailor planning recommendations, ultimately enhancing transport equity and contributing to sustainable urban built environments.